Description of Psychological Well Being in Mothers Who Have Children with Special Needs - Camelia Wahida Syauqi; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2023)
This study aims to determine the description of psychological well-being in mothers who have autistic children and what factors influence psychological well-being. The method used in this research is qualitative with a case study approach. The analysis used is thematic analysis. There were three participants in this study, women aged 20-40 years, had autistic children, and one significant other. The data collection process in this study used semi-structured interviews. The results of this study indicate that even though they are destined to live together with autistic children, the participants in this study have been able to live their lives like a mother in general